Caracterização genotípica do loci alfa globínico de pacientes com microcitose e hipocromia com ou sem anemia - CARLOS, Aline Menezes (2018)
Introduction: The thalassemias, excluding iron deficiency, are the main causes of microcytic anemia worldwide. The α-thalassemia, characterized by genetic alterations affecting the α-globin gene cluster on chromosome 16p13.3, is one of the most widely disseminated hemoglobinopathies in the world. In the last few decades, several methodologies and approaches for the diagnosis these alterations have been developed and applied, such as MLPA (Multiplex Ligation-dependent Probe Amplification), which allows for detection genomic deletions and duplications, known, new or rare of varying sizes. This work seeks to elucidate the molecular basis of cases of microcytic anemia that could not be defined by other traditional methods. Material and Method: Eightyfive patients with microcytosis without iron deficiency and screened for α-thalassemia by multiplex-gap-PCR, were evaluabled using MLPA. Results: Of the 85 patients analyzed by MLPA, 32 (37.65%) had other molecular alterations affecting the α-globin cluster, which had not been identified by PCR. Of these, 13 (15.29%) patients who presented normal genotype in Multiplex-gap-PCR, when analyzed by the MLPA technique, the following molecular alterations were identified: in 10 (11.76%) only 3B (1 patient), 4A (3 patients), 4B (1 patient), African 1 (α212) (2 patients) polymorphisms and association of African 1 (α212) and 3B polymorphisms (1 patient); in two (2.35%) a deletion of the HS-40 regulatory region and its adjacent sequences and in one (1.18%) an extensive duplication involving from the POLR3K-3 region to HBQ1-3. This case resulted in an allele with four expressed α genes (αααα/αα), covering a genomic region of approximately 140 kilobases. In addition to this, in 19 (22.35%) patients that in the Multiplex-gap-PCR had been detected the deletion 3.7, both in heterozygosis and homozygous, when analyzed by the MLPA technique, beyond this deletion were identified in 14 (16.47%) the association with 3A (1 patient), 3B (1 patient), 4A (2 patients), 4B (5 patients), African 1 (α212) (3 patients) polymorphisms, and a combination between 3B and 4B (1 patient) polymorphisms and 1B, 3B and African 1 (α212) (1 patient) polymorphisms. In the other five (5.88%) associations with other deletions were observed. Of which in two (2.35%) a rare deletion of about 67 kilobases of DNA was detected, in the α-gene regulatory region (HS-40) and its adjacent regions (POLR3K-3), one (1.18 %) with an extensive deletion that eliminated both α-genes and their HS-40 regulatory region, with approximately 70 kilobases of DNA, which according to size and approximate breakpoints, this should be a new α0 deletion. And another two (2.35%) associated with a new α+ deletion, which eliminated both the zeta gene and the α2 and α1 pseudogenes, with approximately 17.2 kilobases of DNA, which according to size and approximate breakpoints, if it is a new α+ deletion. Conclusion: The MLPA technique allowed us to clarify the molecular basis of α-thalassemia in patients with obscure microcytosis that had not been identified by multiplex PCR, thereby contributing to the diagnostic conclusion.